Gate-Controlled Rectifying Direction in PdSe2 Lateral Heterojunction Diode - Seo, Dongwook; Seo, Jae Eun; Das, Tanmoy; Kwak, Joon Young; Chang, Jiwon (WILEY, 2021)
The thickness-dependent band structure of 2D materials has enabled the construction of in-plane lateral heterojunction within the same material platform. Simply forming regions of the same 2D material with different thicknesses induces the band offsets in energy bands at the interface to complete the heterojunction. Especially, pentagonal palladium diselenide (PdSe2) can create various combinations of different band gaps due to its widely tunable band gap ranging from 0 to approximate to 1.3 eV. Here, a PdSe2-based gate-controlled rectifier diode realized simply by creating the lateral heterojunction using as-exfoliated PdSe2 flake composed of different thickness regions are reported. Interestingly, by tailoring the heterojunction architecture with a certain combination of the thicknesses, a unique gate-controlled rectification can be observed where the rectifying direction can be tuned by the applied gate bias. The different gate modulation levels in the thin and thick regions leads to the different band bending, respectively. Therefore, adjusting the heterojunction barrier height by the gate bias makes it possible to modulate the direction of dominant current. The demonstration of the reversible rectifying direction paves the way for the realization of essential component in the tunable logic gate.
Keywords: LARGE-AREA; EPITAXIAL-GROWTH; MOS2; LAYERS; SEMICONDUCTOR